Model-based interactive visualization for complex systems requirements and design in joint tests - Chao Sun; Ruo Wu Wu; Si Yuan Liu (SLAS Technology, 2025)
This study presents an interactive visualization-based Model-Based Systems Engineering (MBSE) technique that is especially designed to handle requirements analysis and design issues in joint test settings. Standardized operational requirement description, test requirement analysis, test design, and first test system plan generation are the four primary phases that make up the technique. This method provides a more thorough and approachable depiction of both operational and test requirements by utilizing interactive visualization techniques. This makes it possible for test staff to more accurately and efficiently develop, visualize, and improve test plans. The methodology's efficacy in augmenting the capabilities of joint testing platforms is demonstrated through a thorough case study of a joint test. Higher levels of accuracy and dependability in test results are eventually a result of this approach's strong support for requirements analysis, test design, and the general execution and assessment of joint tests inside complex systems.